Perumpamaan Penabur Benih Sebagai Pendekatan Misi Lintas Budaya Berdasarkan Markus 4:1-20 - Nikolaus Nikolaus; Yohanes Andi; Harming Harming (Integritas: Jurnal Teologi, 2020)
The greatest duty of believers is to preach the gospel. Therefore, various approaches to preaching the gospel, such as helping people who are experiencing natural disasters victims of the earthquake, tsunami and Corona Virus (Covid 19) and also preaching the gospel in accordance with the context of the recipient. So that the motivation of people to become Christians is not because they believe in Jesus. But because of the attitude and not the people who serve it. The formulation of the problem of this research is how the parable of the seed sowing: as an cross-cultural mission approach based on Mark 4: 1-20? The purpose of writing articles is to explain the parable of the seed sower: as a cross-cultural mission approach based on Mark 4: 1-20. By using the literature study method. The literature study method is collecting support information from books, journals and others, which supports sources of information for researching about the parable of the seed sower as a cross-cultural mission approach. The results of this research are: finding a comfortable position, using the opportunity as well as possible, giving confirmation, giving a new understanding, preaching the gospel in a cultural context.